Constraints and creativity: Transforming a live artistic experience for children into Zoom - Jorge Graça; Paulo M. Rodrigues; Helena Rodrigues; Jan Sverre Knudsen (Nordic Journal of Art and Research)
This article explores how the Portuguese ensemble Companhia de Música Teatral (CMT) adapted their live performance PaPI – Opus 8 for Zoom in response to the 2020 COVID-19 pandemic, which severely limited in-person gatherings and artistic events. Originally planned for a nationwide tour, PaPI – Opus 8 faced major challenges due to pandemic restrictions, prompting CMT to rework the piece for an online audience. The result was a transformed version titled PaPI – Opus 8.z, crafted specifically for the Zoom video-conferencing platform. The article gives a detailed examination of this performance piece and its reception, providing a comprehensive understanding of the challenges and achievements associated with the adaptation of this live performance to the virtual realm.